An anti-inflammatory and low fermentable oligo, di, and monosaccharides and polyols diet improved patient reported outcomes in fibromyalgia: A randomized controlled trial - Silva, Ana Rita; Bernardo, Alexandra; de Mesquita, Maria Fernanda; Vaz-Patto, José; Moreira, Pedro; Silva, Maria Leonor; Padrão, Patrícia (Frontiers in Nutrition, 2022)
Background Fibromyalgia (FM) has been associated with dysbiosis and low-grade inflammation. Studies have reported that diet influences clinical features in FM. Objective To evaluate the effect of an anti-inflammatory and low fermentable oligo, di, and monosaccharides and polyols (FODMAP) diet on clinical outcomes of patients with FM. Methods This two arms Randomized Controlled Trial (NCT04007705) included 46 female patients with FM. The intervention group (n = 22) adopted an anti-inflammatory diet for 3 months, excluding gluten, dairy, added sugar, and ultra-processed foods, along with a low FODMAPs diet in the first month. The control group (n = 24) followed general healthy eating recommendations. Both diets were applied by a certified dietitian. Before and after the intervention, participants were assessed regarding pain, fatigue, gastrointestinal symptoms, quality of sleep, and quality of life, through the Revised Fibromyalgia Impact Questionnaire (FIQR), Visual Analogue Pain Scale (VAS), Visual Analog Scale from gastrointestinal symptoms (VAS GI), Brief Pain Inventory (BPI), Pittsburg Sleep Quality Index (PSQI), Fatigue Severity Survey (FSS), and The Short Form Health Survey (SF-36). A blood sample was collected and high-sensitive C-Reactive Protein and Erythrocyte Sedimentation Rate were quantified. Paired Samples t-test/Wilcoxon and independent samples t-test/Mann−Whitney were used to compare variables between groups. Results After intervention, there was an improvement in intervention group scores of FIQR (p = 0.001), VAS (p = 0.002), BPI (p = 0.011), FSS (p = 0.042), VAS_GI (p = 0.002), PSQI (p = 0.048), and SF36 (p = 0.045) compared to control group. Inflammatory biomarkers (hs-CRP, ESR) did not change in both groups. The intervention was beneficial in the intervention group, regardless of age, disease duration, body mass index variation, and body fat change between baseline and post-intervention. Conclusion An anti-inflammatory and low-FODMAP diet improved clinical features in patients with FM and may be useful as a complement to pharmacological therapy. Clinical Trial Registration [https://clinicaltrials.gov/ct2/show/NCT04007705], identifier [NCT04007705].